Use of telepharmacy for the care of people with chronic communicable diseases: a scoping review (Research, Society and Development, 2023)
Clinical services provided by pharmacists are activities whose objective is to optimize the use of medicines, in order to guarantee their effectiveness and safety. The offer of these services can happen in different scenarios in person or remotely. The Covid-19 pandemic expanded the experience of using telepharmacy for continuity of care for patients with chronic diseases. In this sense, this scoping review analyzes perspectives for the provision of clinical pharmaceutical services, remotely, in the care of people with chronic communicable infections. Methods: The searches were carried out in October 2021, in seven literature sources, using a combination of keywords structured from the PCC acronym, that is, Population (people with chronic communicable diseases, especially hepatitis B), Concept (telemedicine or telepharmacy), Context (clinical services provided by pharmacists, in outpatient clinics, households or community pharmacies). Results: From 428 records identified in the searches, 6 studies were selected according to the eligibility criteria, with examples of different clinical services and evaluation of outcomes such as patient satisfaction, treatment adherence, clinical and economic results. Conclusion: Telepharmacy initiatives can be highly satisfactory, from the point of view of professionals and users, presenting advantages and some limitations. However, few studies were identified in which the pharmacist works in the monitoring of people with chronic communicable diseases. Thus, it is important to conduct implementation studies and methodologically more robust studies that assess the effectiveness and impact of the use of telepharmacy in health systems.